Business process management : 11th International Conference, BPM 2013, Beijing, China, August 26-30, 2013. Proceedings - Wang, Jianmin; Weber, Barbara; Daniel, Florian (Lecture Notes in Computer Science, 2013)
This book constitutes the proceedings of the 11th International Conference on Business Process Management, BPM 2013, held in Beijing, China, in August 2013. The 17 regular papers and 8 short papers included in this volume were carefully reviewed and selected from 118 submissions. The papers are organized in 7 topical sections named: process mining; conformance checking; process data; process model matching; process architectures and collaboration; as well as alternative perspectives, and industry paper.